Movement analysis iof the flat and the undulating breaststroke pattern - Persyn, U.; Colman, V.; Van Tilborgh, L. (Biomechanics and Medicine in Swimming. Swimming Science VI, 1992)
A new video-analysis system was used to derive hypotheses regarding advantages of an extremely undulating breaststroke pattern. To obtain supporting evidence on the effectiveness of undulation, relationships between several specific body segment positions (or angles) in the stroke and resultant impulses per phase (difference between propulsion and drag) were specified (Tau-B coefficients, significant at the 5% level). In the stroke cycle of the undulating pattern of an 'experimental' swimmer, higher peaks and less decrease in velocity of the centre of gravity are seen. Apparently, this is obtained due to a vertical propeller-like propulsion of the hands and feet, and up- and downhill movements of the entire body. The following correlations were found between impulse and respectively the amount of upward spreading of the arms (0.44), the amount of keeping the hands in front of the vertical under the shoulders (0.38), the depth of closing the legs (0.47), the more vertical foot position (0.41), the amount of the most downhill (0.59) and uphill trunk position (0.37). Although this uphill, hydroplaning position takes place in the recovery phases, the symmetry in the undulation of the body is not significantly disturbed and the vertical displacements of the centre of gravity are small.